Systems change in the context of an initiative to scale up Housing First in Canada. Issue 1 (12th June 2018) - Nelson, Geoffrey; Worton, S. Kathleen; Macnaughton, Eric; Tsemberis, Sam; MacLeod, Tim; Hasford, Julian; Goering, Paula; Stergiopoulos, Vicky; Aubry, Tim; Distasio, Jino
Abstract: In this study, we examine changes in the homeless‐serving system in the context of a training and technical assistance initiative to scale up Housing First (HF) in 6 Canadian communities. Based on qualitative data from focus groups and individual interviews with key stakeholders (k = 7, n = 35) and field notes gathered over a 3‐year period (n = 146), we found 2 main system changes: (a) changes in the capacity of the service delivery system at multiple levels of analysis (from individual to policy) to implement HF, and (b) changes in the coordination of parts of the service delivery system and collaboration among local stakeholders to enhance HF implementation. These changes were facilitated or constrained by the larger context of evidence, climate, policy, and funding. The findings were discussed in terms of systems change theory and implications for transformative systems change in the mental health and homelessness sectors.